-17m-11=-9m-59

Simple and best practice solution for -17m-11=-9m-59 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -17m-11=-9m-59 equation:


Simplifying
-17m + -11 = -9m + -59

Reorder the terms:
-11 + -17m = -9m + -59

Reorder the terms:
-11 + -17m = -59 + -9m

Solving
-11 + -17m = -59 + -9m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '9m' to each side of the equation.
-11 + -17m + 9m = -59 + -9m + 9m

Combine like terms: -17m + 9m = -8m
-11 + -8m = -59 + -9m + 9m

Combine like terms: -9m + 9m = 0
-11 + -8m = -59 + 0
-11 + -8m = -59

Add '11' to each side of the equation.
-11 + 11 + -8m = -59 + 11

Combine like terms: -11 + 11 = 0
0 + -8m = -59 + 11
-8m = -59 + 11

Combine like terms: -59 + 11 = -48
-8m = -48

Divide each side by '-8'.
m = 6

Simplifying
m = 6

See similar equations:

| 7x+9=29-3x | | 3x+8=38-2x | | x-2+3=12 | | 3(2x+1)-4(x-2)=25 | | f(x)=-3x^2+15 | | 5*5+7-3= | | 110=w(w+15) | | W^2+15w=110 | | 4xy-4xz= | | t^2-3t=-2 | | 2=16-2p | | 12y^2+y-20=0 | | 1.5x+14=26+0.5x | | 5x+18=12x+4 | | 7w-3(4w+8w)=11 | | 0=-2475+29x^2 | | 6x-3=7+5x | | 1000=-4+2x | | 2(x+39)=3(2x+2) | | 6x+48=8x+40 | | 16x-(4x-1)(4x-1)(4x-3)=29 | | 0=-3x^2+28x+144 | | 36=3w+2 | | 30=x+y+2 | | c-.015c=102 | | x+3/4-x/2=3 | | 0=-x^3+14x^2+144x-7000 | | 6-(v-3)=9(2v+3) | | 7(6x-7)+1=42x | | 10x^2-25x^3=0 | | 8+2n+1= | | x+15=420 |

Equations solver categories